Instability of revised Korean Developmental Screening Test classification in first year of life - Ji Eun Jeong; You Min Kim; Na Won Lee; Gyeong Nam Kim; Jisuk Bae; Jin Kyung Kim (Clinical and Experimental Pediatrics)
Background Early development is characterized by considerable variability. Purpose This study aimed to examine the stability of developmental classifications using the revised Korean Developmental Screening Test (K-DST) in healthy term infants aged 4–6 and 10–12 months. Methods Data were obtained from the Korean Children’s Environmental Health Study, a nationwide prospective birth cohort. Sixty-nine healthy term infants (26 boys, 43 girls) underwent serial K-DST assessments at 4–6 and 10–12 months of age, between August 2017 and December 2019 Results At 4–5 months, over 50% of infants were categorized in the ≥-1 standard deviation (SD) group, with the lowest prevalence in the gross motor domain (52.7%). Seven infants (10.1%) scored below -2 SD in at least one domain, most commonly in gross and fine motor domains (7.3%). At 10–12 months, over 70% of infants scored in the ≥-1 SD group, except in the language domain. Six infants (9.5%) scored below -2 SD in at least one domain, (cognition 4.8%, language 3.2%, gross motor 3.2%). Serial follow-up showed significant improvement, with many infants moving to the ≥-1 SD group, particularly in the gross motor domain (33.3%). Of the seven infants scoring below -2 SD at 4–5 months, only two remained in this category at 10–12 months. Conclusion Infants scoring below -2 SD on the revised K-DST 4–5 months questionnaire, especially in the gross motor domain, should undergo close monitoring and repeated evaluations in the absence of neurological abnormalities or developmental red flags.